1991
DOI: 10.1128/mcb.11.2.1092
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the extent of splicing of influenza virus NS1 mRNA: role of the rates of splicing and of the nucleocytoplasmic transport of NS1 mRNA.

Abstract: Influenza virus NS1 mRNA is spliced by host nuclear enzymes to form NS2 mRNA, and this splicing is regulated in infected cells such that the steady-state amount of spliced NS2 mRNA is only about 10% of that of unspliced NS1 mRNA. This regulation would be expected to result from a suppression in the rate of splicing coupled with the efficient transport of unspliced NS1 mRNA from the nucleus. To determine whether the rate of splicing of NS1 mRNA was controlled by trans factors in influenza virus-infected cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…One hypothesis is that the 775-to-860 region in the 3' exon acts as a spacer to allow adjacent regions of NS1 mRNA to interact to form a sec- In influenza virus-infected cells, the extent of splicing of NS1 mRNA is regulated such that the steady-state amount of spliced NS2 mRNA is about 10% of that of unspliced NS1 mRNA (20,23). This regulation most likely results from a suppression in the rate of splicing coupled with the efficient transport of unspliced NS1 mRNA from the nucleus (1, 2,27,30). Recent experiments have shown that the rate of splicing of NS1 mRNA in infected cells is almost certainly controlled solely by cis-acting sequences in NS1 mRNA itself and is independent of trans-acting factors (2).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that the 775-to-860 region in the 3' exon acts as a spacer to allow adjacent regions of NS1 mRNA to interact to form a sec- In influenza virus-infected cells, the extent of splicing of NS1 mRNA is regulated such that the steady-state amount of spliced NS2 mRNA is about 10% of that of unspliced NS1 mRNA (20,23). This regulation most likely results from a suppression in the rate of splicing coupled with the efficient transport of unspliced NS1 mRNA from the nucleus (1, 2,27,30). Recent experiments have shown that the rate of splicing of NS1 mRNA in infected cells is almost certainly controlled solely by cis-acting sequences in NS1 mRNA itself and is independent of trans-acting factors (2).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the influenza virus M1 and NS1 mRNAs are spliced by the cellular splicing machinery indicates that splicing can be uncoupled from transcription by the cellular RNA polymerase II+ However, the splicing of these two single intron viral mRNAs is inefficient: The steady-state amount of the spliced mRNA products is only about 10% of that of the unspliced mRNA precursors (Lamb et al+, 1980(Lamb et al+, , 1981+ Incomplete splicing is necessary because both the spliced and unspliced mRNAs are exported to the cytoplasm and are translated into virus-specific proteins (reviewed in Krug et al+, 1989)+ The results presented here provide an explanation for the inefficient splicing of these two single-intron influenza viral mRNAs: this splicing is not coupled to CPSF-dependent 39-end formation+ In addition, splicing which is uncoupled from polymerase II transcription may be intrinsically inefficient+ Finally, because the export of the unspliced NS1 and M1 mRNAs in influenza virus-infected cells is rapid (Alonso-Caplen & Krug, 1991), some mechanism may efficiently remove these viral mRNAs from the cellular splicing machinery+…”
Section: Implications For the Splicing Of Viral Mrnas In Influenza VImentioning
confidence: 99%
“…This suggests that at least for these viruses, the splicing of NS1 mRNA depends solely on a cis-acting sequence in the NS1 mRNA itself, consistent with the results obtained from in vitro splicing of NS1 mRNA (Nemeroff et al, 1992) and the NS2 protein functioning from the early phase of infection. The splicing of NS1 mRNA has also been shown to depend on the efficiency of nucleocytoplasmic transport of the unspliced NS1 mRNA (Alonso-Caplen & Krug, 1991).…”
Section: Introductionmentioning
confidence: 99%